Peningkatan Pengetahuan dan Keterampilan Manajemen Pada Pelaku UMKM Desa Balesari Kabupaten Magelang - Hanung Eka Atmaja; Budi Hartono; Khairul Ikhwan (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
The community service program carried out in Balesari Village, Windusari District, Magelang Regency,aims to solve mismanagement problems that occur in terms of financial administration, marketing, and human resources. Preliminary observations have been made before, which found that MSMEs in this village still receive minimal guidance in the form of small business management. By knowing the mapping of constraints or problems experienced by MSME actors, it is hoped that they can obtain accurate training materials so that these MSMEs can develop forward and encourage the economy of the surrounding community. The method used is the tutorial and discussion extension method. The material presented is about the basics of management science in business. MSMEs require good knowledge of human resource management, marketing management, and financial management for the progress of their business. MSME owners or managers are expected to have skills in managing their human resources, as well as the ability to manage facilities and infrastructure in their businesses. If MSME managers have good management knowledge, it will make it easier for their business to continue to develop and be adaptive in facing all the demands of changing times. Therefore, this community service is carried out by assisting related partners to develop their business and to be able to compete with other MSMEs. The flow of activities, namely the delivery of material, training, and assistance on the basics of management science. As a result ofthis dedication, the partners who received admitted aid that they had a better understanding of how to design effective and efficient marketing strategies, how to manage finances in a simple manner, and a little understanding of how to design suitablehuman resource needs